Reduplikasi pada Novel Konspirasi Alam Semesta Karya Fiersa Besari - Amelia, Citra Anisa; Wahyuni, Septi Sri; Samaya, Doni (Universitas Negeri Padang, 2025)
Reduplication is the process of forming words by duplicating all free morphemes (total repetition) or part of the free morphemes (total repetition). This research on reduplication is to find out whether the written reduplication is correct or not. Because many people don't understand, so they can't differentiate whether the reduplication is a reduplication or just a basic word. In this approach, a qualitative approach is used with descriptive methods. In collecting data, this research carried out documentation techniques on the novels being analyzed. Data validity techniques in this research were assisted by supervisors who aimed to prove the validity of the research results. This data analysis technique used content analysis techniques. Reduplication in the novel Conspiracy of the Universe by Fiersa Besari found a total of 137 data findings. There were 64 complete reduplications, 6 partial reduplications, 14 phoneme change reduplications, and 54 reduplications with affixation. Keywords: reduplication, novel